2003
DOI: 10.1111/j.1572-0241.2003.07513.x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Red Wine Extracts Inhibit The Growth of Caga+ Strains of Helicobacter Pylori in Vitro

Abstract: In 1994, Helicobacter pylori was classified as a group I carcinogen and a definite cause of gastric cancer in humans by the International Agency for Research on Cancer (1). Since then, H. pylori has been epidemiologically linked to adenocarcinoma of the distal stomach (2,3), and a recent study has also found a positive association between H. pylori infection and colorectal adenomas (4). CagA is the strain-specific H. pylori gene that has been linked to the development of premalignant and malignant histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 5 publications
1
61
0
3
Order By: Relevance
“…Phenolic compounds in grape products play important roles for antioxidant, anti-inflammatory, and antimicrobial effects (13,18,20). In this study, muscadine grape seed extract contained the highest total phenolic content (645.5 mg GAE/g dw), followed by muscadine synergy and skin extracts (381.9 and 135.0 mg GAE/g dw, respectively).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Phenolic compounds in grape products play important roles for antioxidant, anti-inflammatory, and antimicrobial effects (13,18,20). In this study, muscadine grape seed extract contained the highest total phenolic content (645.5 mg GAE/g dw), followed by muscadine synergy and skin extracts (381.9 and 135.0 mg GAE/g dw, respectively).…”
mentioning
confidence: 86%
“…Grapes (Vitis vinifera), well known for their high levels of antioxidants and polyphenols, have also shown promise as novel antimicrobial agents. A few studies have already reported the anti-H. pylori activities of grape seed and wine, including an active chemical constituent (e.g., resveratrol, a stilbene from red wine) (13). However, no effort has been made to evaluate the grape skin or different grape types (e.g., table and muscadine grapes).…”
mentioning
confidence: 99%
“…Epigallocatechin gallate, one of the green tea catechins, showed significant cytoprotective effects against H. pylori associated gastric cytotoxicity [163] . Red wine and resveratrol have also been shown to inhibit the growth of H. pylori cagA+ strains in vitro [164] . In an openlabel RCT, adding vitamin C and E to antibiotic regimens showed excellent H. pylori eradication rates.…”
Section: Eradication: Hope Is Coming?mentioning
confidence: 99%
“…Herbal extracts and essential oils have been used as traditional medicines for thousands of years all over the world, and their anti-H. pylori activity has been widely demonstrated in vitro (2)(3)(4)(5). Many foodstuffs have also exhibited inhibitory activity against the growth of H. pylori in vitro, among others, red wine (6,7), sprouted peas (8), green tea (9), and cranberry juice (10). In many cases, the antibacterial activity of both herbal extracts and foodstuffs has been associated with their content in phenolic compounds, in particular, flavonoids (11)(12)(13), resveratrol (6), and hydrolyzable tannins (14).…”
Section: Introductionmentioning
confidence: 99%
“…Many foodstuffs have also exhibited inhibitory activity against the growth of H. pylori in vitro, among others, red wine (6,7), sprouted peas (8), green tea (9), and cranberry juice (10). In many cases, the antibacterial activity of both herbal extracts and foodstuffs has been associated with their content in phenolic compounds, in particular, flavonoids (11)(12)(13), resveratrol (6), and hydrolyzable tannins (14). The mechanism by which phenolic compounds affect the growth of H. pylori is unknown, but different theories have been proposed, for example, inhibition of the urease activity (15), adhesion to human gastric mucus (10), disintegration of the outer membrane (16), and inhibition of VacA citotoxin activity which causes the development of inflammation and ulceration in patients (17,18).…”
Section: Introductionmentioning
confidence: 99%